FISH MEASURING BOARD FOR RACIAL INVESTIGATIONS - Noble, A (Indian Journal of Fisheries, 2011)
To measure the linear dimensions other than the total length of a fishfor racial investigations, a board is designed and got fabricated. It has a mirrorbase and a half metre scale. There is a grooved wheel and two pulleys at itsback, carrying a steel tape with a needle wire fixed at its zero. When thewheel is rotated the tape runs from left to right and the needle rides over thefish on the board. The tape gives the measurement and the rider helps topin-point it avoiding parallax error. The board is waterproof, inexpensive andeasy to make.